NEED FOR PROVISION OF PSYCHOSOCIAL SUPPORT SERVICES TO NURSES WORKING IN EMERGENCY SECTIONS OF GOVERNMENT HOSPITALS - Aslam, Naeem (Journal of Ayub Medical College Abbottabad, 2011)
Nursing is a one of the highly stressful occupation.1 High levels of occupational stress are believed to affect the physical and mental health of nurses. Constantly working in the emergency departments, nurses show higher level of psychological distress, burnout and are more prone to develop psychiatric problems.2 These psychiatric problems are commonly manifested in the form of anger, tension, uptightness, low mood, exhaustion, and avoidance symptoms. In a comparative study, it was found that nurses working in emergency wards have a higher stress level compared to the control sample.3 They face greater work pressure and worse health responsibility and realisation of a health-promoting lifestyle. In addition, working in an inpatient department appears to be a potent stressor for nurses.4 It is also evident that nurses working morning shifts showed higher stress levels, and poor sleep quality as stress level is directly correlated to sleep.5 Although all nurses undergo the stressful situation, the younger nurses had more nursing stress than older nurses.6 Although psychosocial health issues of nurses and its intervention has been studied extensively in the US and Europe, there is a need to explore these factors from the Pakistani perspective. This editorial is aimed to raise the interest on the psychosocial problems of the nurses working in the emergency units of government hospitals. Occupational stress among nurses is the result of exposure to a combination of working environment and personal factors. For example, role boundary and role insufficiency were the factors that had the highest association with occupational stress.7 High rates of emotional exhaustion in nurses were found to be predicted by young age, high psychological job demands, low psychological job control, low social support at the workplace, and job strain.8 It is recommended to conduct researches to identify organizational, family or social factors which contribute to reduction of perceived occupational stress and increase job satisfaction and job performance among the nurses and specifically those who work in the emergency units of the hospitals. For intervention, occupational training programmes and occupational health education is necessary to improve the knowledge and ability of nurses to cope with job demands and reduce occupational stress.7 Cognitive-behavioural stress management training program on stress reduction among nurses are quite effective.1 In addition, psychological assessment can be helpful for identification of the problems. On the basis of assessment, individual counselling sessions can be provided to those who have psychological problems, are more vulnerable and/or at risk. Moreover, Workshops and seminars on the issues like, work motivation, anger management, personal management, and communication skills can be helpful for the nurses. Nurses’ realisation of a health-promoting lifestyle9 can be achieved through good relationships and appropriately increase employment of nurses through a good work atmosphere in hospitals. These strategies will have implications and the long term effects. It will have not only the positive effect on the nurses, but also it will improve the nurse-patient relationship. Ultimately, overall performance of the organization will be enhanced